Make libraries from armouries... - Lostáková, Dana (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
Social and political changes after the revolution in November 1989 helped to accomplish the old message - ¨Make libraries from armouries...¨ (J.A. Comenius) - which could thus be inscribed into the pavement of the courtyard of the one-time military armoury, and present-day Information Centre of the Palacký University in Olomouc.